Meningkatkan Komunikasi Proses Belajar Mengajar Melalui Diskusi Tanya Jawab Dalam Membentuk Karakter Siswa Di SMP Negeri 18 Medan - Haratua Aritonang (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Communication is needed by almost all human activities, wherever they are, they are always touched by communication. Education cannot run without the support of communication, even education can only work through communication.